Marr's Attacks: On Reductionism and Vagueness. (5th March 2015) - Eliasmith, Chris; Kolbeck, Carter
Abstract It has been suggested that Marr took the three levels he famously identifies to be independent. In this paper, we argue that Marr's view is more nuanced. Specifically, we show that the view explicitly articulated in his work attempts to integrate the levels, and in doing so results in Marr attacking both reductionism and vagueness. The result is a perspective in which both high‐level information‐processing constraints and low‐level implementational constraints play mutually reinforcing and constraining roles. We discuss our recent work on Spaun—currently the world's largest functional brain model—that demonstrates the positive impact of this kind of unifying integration of Marr's levels. We argue that this kind of integration avoids his concerns with both reductionism and vagueness. In short, we suggest that the methods behind Spaun can be used to satisfy Marr's explicit interest in combining high‐level functional and detailed mechanistic explanations.